Photonic band gap properties of one-dimensional photonic quasicrystals containing Nematic liquid crystals - Y. Trabelsi; N. Ben Ali; Francis Segovia-Chaves; Herbert Vinck Posada (Results in Physics, 2020)
Reflectance spectra of one-dimensional periodic multilayered stacks with anisotropic defect layer built according to the Generalized Thue Morse sequence is investigated by the theoretical transfer matrix method for both polarized waves. The main hetero-layers of the structure are made up using SiO2 and Bi4Ge3O12 materials. The photonic quasicrystal reveal an interesting reflectance spectra for specific generation (m = n, n) of the Generalized Thue Morse sequence and layers thicknesses. Upon increasing the deformed thicknesses a significant enhance of the photonic band gap is shown and an improvement of the optical properties of the photonic crystal slab is observed. By applying homogeneously Nematic Liquid Crystal as defects into the photonic quasicrystals, a tunable resonant transmission can be notably opened and it is very sensitive to the thicknesses of incorporated Nematic Liquid Crystal. These results may be useful for tunable quasi-photonic Bragg reflectors.